Novel Associations in Disorders of Sex Development: Findings From the I-DSD Registry - GÜRAN, TÜLAY (ENDOCRINE SOC, 2014)
Context: The focus of care in disorders of sex development (DSD) is often directed to issues related to sex and gender development. In addition, the molecular etiology remains unclear in the majority of cases. Objective: To report the range of associated conditions identified in the international DSD (I-DSD) Registry. Design, Setting, and Patients: Anonymized data were extracted from the I-DSD Registry for diagnosis, karyotype, sex of rearing, genetic investigations, and associated anomalies. If necessary, clarification was sought from the reporting clinician. Results: Of 649 accessible cases, associated conditions occurred in 168 (26%); 103 (61%) cases had one condition, 31 (18%) had two conditions, 20 (12%) had three conditions, and 14 (8%) had four or more conditions. Karyotypes with most frequently reported associations included 45, X with 6 of 8 affected cases (75%), 45, X/46, XY with 19 of 42 cases (45%), 46, XY with 112 of 460 cases (24%), and 46, XX with 27 of 121 cases (22%). In the 112 cases of 46, XY DSD, the commonest conditions included small for gestational age in 26 (23%), cardiac anomalies in 22 (20%), and central nervous system disorders in 22 (20%), whereas in the 27 cases of 46, XX DSD, skeletal and renal anomalies were commonest at 12 (44%) and 8 (30%), respectively. Of 170 cases of suspected androgen insensitivity syndrome, 19 (11%) had reported anomalies and 9 of these had confirmed androgen receptor mutations. Conclusions: Over a quarter of the cases in the I-DSD Registry have an additional condition. These associations can direct investigators toward novel genetic etiology and also highlight the need for more holistic care of the affected person.
Keywords: ANDROGEN INSENSITIVITY SYNDROME; LEMLI-OPITZ-SYNDROME; GENITAL ANOMALIES; HYPOSPADIAS; KIDNEY; STEROIDOGENESIS; MALFORMATIONS; EPIDEMIOLOGY; MANAGEMENT; GENES